1992
DOI: 10.1128/iai.60.2.523-528.1992
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous tumor necrosis factor, interleukin-6, and gamma interferon levels during Listeria monocytogenes infection in mice

Abstract: Mice were infected intravenously with a sublethal dose of Listeria monocytogenes cells and then levels of tumor necrosis factor (TNF), interleukin-6 (IL-6), and gamma interferon (IFN-y) in the bloodstreams, spleens, and livers were monitored. The maximum level of TNF was detected at 72 h in the spleens and livers, but TNF was never detected in the bloodstreams. IL-6 appeared in the bloodstreams and spleens and peaked at 48 h. The maximum level of IFN-y could be detected in all three specimens, and the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(78 citation statements)
references
References 22 publications
(41 reference statements)
3
75
0
Order By: Relevance
“…Thus, the decrease in TNF levels was not correlated with an inhibitory effect on IL-6 production, at least at the 1.5 h time point. At the peak of the response (at 2.5 h) a strong inhibition in the TNF yield by CsA produced a slight decrease in the IL-6 titer, namely in normal or galactosamine-treated mice ( Table 2) confirming that IL-6 production can be dissociated from TNF levels in the blood as already reported under various experimental conditions [20,27,28]. In contrast, in adrenalectomized mice, CsA injection produced a marked inhibition of serum IL-6 level early after the LPS challenge indicating a differential sensitivity to CsA of IL-6-producing cells in the absence of endogenous glucocorticoids.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, the decrease in TNF levels was not correlated with an inhibitory effect on IL-6 production, at least at the 1.5 h time point. At the peak of the response (at 2.5 h) a strong inhibition in the TNF yield by CsA produced a slight decrease in the IL-6 titer, namely in normal or galactosamine-treated mice ( Table 2) confirming that IL-6 production can be dissociated from TNF levels in the blood as already reported under various experimental conditions [20,27,28]. In contrast, in adrenalectomized mice, CsA injection produced a marked inhibition of serum IL-6 level early after the LPS challenge indicating a differential sensitivity to CsA of IL-6-producing cells in the absence of endogenous glucocorticoids.…”
Section: Discussionsupporting
confidence: 80%
“…Preparation of spleen homogenates [27] Spleens that had been stored at ÿ 208C were disrupted in a glass homogenizer to give 20% suspensions in ice-cold Earle's balanced salt solution (BSS; GIBCO Life Technologies Ltd, Paisley, UK) containing 1% (w/v) 3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulphonate (CHAPS; Sigma). Suspensions were left overnight on ice, clarified by centrifugation in a microfuge and assayed for TNF.…”
Section: Tnf Assaymentioning
confidence: 99%
“…We also investigated the detection of VIP and SP in the livers of T. paurometabolum-injected mice. Our previous study [29] showed that the granulomas developed in the liver, spleen and lung until 3 weeks after injection, and thereafter regress in these ani- mals. Therefore, mice were injected intravenously with 10 V cfu of viable T. paurometabolum in saline, and formalin-¢xed para¤n-embedded sections of the livers were obtained from the mice on day 21 of injection.…”
Section: Detection Of Neuropeptides In the Livers Of T Paurometabolumentioning
confidence: 87%